A Practical Method for Accurate Measurement of Trace Level Fluorine in Mg‐ and Fe‐Bearing Minerals and Glasses Using Electron Probe Microanalysis. Issue 3 (19th January 2016) - Zhang, Chao; Koepke, Jürgen; Wang, Lian‐Xun; Wolff, Paul E.; Wilke, Sören; Stechern, André; Almeev, Renat; Holtz, Francois
Abstract : Fluorine plays an important role in magmatic and hydrothermal processes, but due to its low abundance in geological samples determining F is difficult by electron probe microanalysis. By using a W‐Si multi‐layered pseudocrystal as the diffraction crystal instead of thallium acid phthalate (TAP), count rates were considerably higher, which however introduced spectral interferences between F K α and Fe L α and Mg K β lines when normal integral mode is applied. In this study, we developed a protocol using a W‐Si multi‐layered pseudocrystal for measuring accurately trace level F in both minerals and glasses. First, we used differential mode with an optimised PHA (pulse height analysis) setting in signal processing, instead of normal integral mode, which completely eliminated the second‐order Mg K β line. Second, the overlap of the first‐order Fe L α on F K α peak, which cannot be filtered by modifying the PHA setting, was calibrated quantitatively using F‐free minerals and silicate glasses. Applying this two‐step method, F was determined in a number of reference glasses, as well as in glasses synthesised from powders of the rock reference materials AC‐E, GS‐N and DR‐N. Our data are consistent within error with F concentrations determined by other methods, demonstrating the reliability of this method. Key Points: Spectral scans with integral mode show overlaps from Fe X‐ray lines on the FKa peak and its left‐side background, as well as overlaps from Mg X‐ray lines on the FKa right‐side background. Using differential mode can diminishes Mg X‐ray lines on the FKa right‐side background. Overlaps from Fe X‐ray lines for determining F are calibrated in this study.